2021
DOI: 10.1002/jssc.202001199
|View full text |Cite
|
Sign up to set email alerts
|

A green molecular imprinted solid‐phase extraction protocol for bisphenol A monitoring with HPLC‐UV to guarantee the quality and safety of walnuts under different storage conditions

Abstract: Monitoring the residual toxicant concentrations in foods is the key step for minimizing potential hazards. The huge interest about food contamination and exposure to endocrine disruptors such as bisphenol A has emerged the development of sensitive analytical methodologies to guarantee the safety and quality of foods. In this work, a green molecularly imprinted solid-phase extraction protocol coupled with high-performance liquid chromatography with UV detection was optimized following the principles of green an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Various matrices are in the spotlight of different research groups for the determination of BPA and its analogs in literature. These include environmental samples, food samples as well as matrices of bioanalytical interest [8][9][10][11]. Different analytical techniques have been used for the determination of bisphenol analogs in numerous samples.…”
Section: Introductionmentioning
confidence: 99%
“…Various matrices are in the spotlight of different research groups for the determination of BPA and its analogs in literature. These include environmental samples, food samples as well as matrices of bioanalytical interest [8][9][10][11]. Different analytical techniques have been used for the determination of bisphenol analogs in numerous samples.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC is one of the most widely used methods for detecting BPs [25–27], particularly when coupled with MS [28]. Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC is one of the most widely used methods for detecting BPs [25][26][27], particularly when coupled with MS [28]. Li et al reported using β-cyclodextrin polymer as the sorbent for solid phase extraction, HPLC with an ultraviolet detector (UV) could achieve analysis of BPA, BPF, and BPAF in water samples and orange juice with limits of detection (LODs) of 0.15 ng/ml [29].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, recognition regions are synthesized by the imprinting process, which generates a highly selective sorbent compared to other compounds with a similar structure [6]. Due to their exceptional selectivity, MIPs have been utilized as sorbents in the molecularly imprinted solid‐phase extraction (MISPE) technique for the recognition, separation, extraction, and purification of various compounds [10]. MIPs have become prevalent due to multiple benefits and characteristics such as fast kinetics, acidic and basic media stability, thermal stability, chemical, and mechanical durability, broad solvent adaptability, high loading capacity and specificity, simplicity of synthesis, and low cost [9].…”
Section: Introductionmentioning
confidence: 99%